2019
DOI: 10.3390/w11050905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multicollinearity on the Bivariate Frequency Analysis of Annual Maximum Rainfall Events

Abstract: A rainfall event, simplified by a rectangular pulse, is defined by three components: the rainfall duration, the total rainfall depth, and mean rainfall intensity. However, as the mean rainfall intensity can be calculated by the total rainfall depth divided by the rainfall duration, any two components can fully define the rainfall event (i.e., one component must be redundant). The frequency analysis of a rainfall event also considers just two components selected rather arbitrarily out of these three components.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Machine learning modelling accuracy can be impacted by multi-collinearity problems if a high correlation exists between feature variables [ 45 ]. It has been found that light absorbance for a specific wavelength is highly correlated to the neighbouring wavelengths, and correlation gradually decreases to far wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning modelling accuracy can be impacted by multi-collinearity problems if a high correlation exists between feature variables [ 45 ]. It has been found that light absorbance for a specific wavelength is highly correlated to the neighbouring wavelengths, and correlation gradually decreases to far wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Multi-collinearity arises when inter-correlation between input features is strong [27,28]. It can be a problem in statistical analysis such as regression as it distorts the prediction results of the model [27,28].…”
Section: Multi-collinearitymentioning
confidence: 99%
“…Nonetheless, feature selection that is not derived from the physical or biological processes related to target variables may give poor performances to the models [16,25,26]. Moreover, pre-selection of features without considering the statistical characteristics such as multi-collinearity can be an obstacle to developing a robust model [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…But majority of the studies in transportation engineering that uses multiple linear regression did not pay much attention to this multicollinearity problem. Studies in others fields like water resources engineering [19,20], electrical engineering [21] and tourism management [22] reported various methods like ridge regression, partial least squares regression and principal component regression to overcome the multicollinearity problem. In this study, we proposed a simple method of defining new variables as a linear combination and ratio of existing independent variables, which not only remove the multicollinearity problem but also help to achieve high R 2 value and significant p values.…”
Section: Introductionmentioning
confidence: 99%